21st century workforce development summit - Adams, Teresa M.; Toledo-Duran, Edwin Josue; Wittwer, Ernie F. (National Center for Freight and Infrastructure Research and Education, 2009)
The transportation workforce will be facing severe strains over the next decade as the baby boom generation begins to retire. These strains will be made worse by the relatively small numbers of workers entering the transportation workforce and the small number entering the technical fields that are the source of the workforce. At the same time the nature of the transportation industry is changing producing the need for new and broader skill sets. These issues were explored in a workshop. It was concluded that new skills will be required. To produce those skills and the number of workers required, new partnerships will also be needed. Agencies, private sector firms and educators will have to combine forces to make the training and development processes as effective as possible and to attract students to the sciences and to transportation in particular.
59 p.
Keywords: Personnel development; Labor force; Transportation careers; Training